Biological oxygen sensing via two-photon absorption by an Ir(III) complex using a femtosecond fiber laser. (30th August 2016) - Moritomo, Hiroki; Fujii, Akinari; Suzuki, Yasutaka; Yoshihara, Toshitada; Tobita, Seiji; Kawamata, Jun
Abstract: Near-infrared two-photon absorption of the phosphorescent Ir(III) complex (2, 4-pentanedionato-κ O 2, κ O 4 )bis[2-(6-phenanthridinyl-κ N )benzo[ b ]thien-3-yl-κ C ]iridium (BTPHSA) was characterized. It exhibited a 800–1200 nm two-photon absorption band, and thus could be electronically excited by 1030-nm femtosecond Ti:sapphire and Yb-doped fiber lasers. By using BTPHSA, oxygen concentrations in human embryonic kidney 293 (HEK293) cells were imaged. These results demonstrate two-photon oxygen sensing of live tissues via easily operable excitation sources.